Use of virtual and augmented reality technologies as a tool for enhancing the competitiveness of the interior design business - Kravchenko, Olesia (Здобутки економіки: перспективи та інновації, 2025)
The modern interior design business faces a high level of competition and constantly changing consumer demands, which necessitate the implementation of innovative technologies to enhance the efficiency of company operations. The use of virtual and augmented reality technologies has become particularly relevant, as they enable the creation of interactive projects, improve communication with clients, and optimize the decision-making process in interior design. The purpose of this article is to provide a comprehensive analysis of the possibilities for applying VR and AR technologies to enhance the competitiveness of the interior design business, identify their advantages and limitations, and assess their practical impact on business processes and client interactions. Methods. The study employs a systematic approach to evaluate the integration of VR and AR into the operations of interior design studios and a comparative analysis of practical cases demonstrating different strategies for implementing virtual and augmented solutions in the interior design process. Additionally, an analytical review of contemporary scientific publications and practical examples was conducted, allowing for the systematization of data regarding the impact of these technologies on client engagement and the speed of design decision-making. Results. The research indicates that the implementation of VR and AR technologies significantly enhances project visualization quality, reduces the time required to coordinate decisions with clients, and provides a more personalized approach tailored to each client. Moreover, the use of interactive tools contributes to increased client loyalty, expansion of the order portfolio, and creation of competitive advantages in the market. It was found that the most effective strategies are combined approaches that integrate VR tours with AR demonstrations of materials and furniture, allowing the virtual experience to closely approximate reality. Conclusions. The use of virtual and augmented reality technologies is an effective tool for enhancing the competitiveness of the interior design business, as it optimizes design processes, improves client interaction, and creates additional value for the customer. The further development and adaptation of VR and AR technologies as immersive tools will contribute to enhancing the innovative potential of companies and ensuring sustainable competitive advantages in the interior design market.